Consistency and Coherence of Turtle Conservation Policies in Venu Island Wildlife Sanctuary, Kaimana, West Papua - Zeth Parinding; Sambas Basuni; Herry Purnomo; Nandy Kosmaryandi; Yusli Wardiatno (Jurnal Manajemen Hutan Tropika, 2016)
Policy management of turtle conservation in the region of Venu Island Wildlife Sanctuary, Kaimana, West Papua is indispensable. Therefore, this study aimed at examining the turtle conservation policy and it’s implementation, both the consistency and coherence. The analytical method used is content analysis and simple mathematic statistics. The consistency of turtle conservation management policies is found inconsistent in implementation. Similarly, coherence between the policy on turtle conservation management with government policy is found incoherent, as it is more oriented to "economic growth" compared to turtle conservation management. This is due to weak management, among others: communication, resources, attitudes and behavior, and bureaucratic structures. "Management Authority Multi-stakeholder" was found as a form of the collaborative approach in carrying out the turtle conservation among institutional managers with other key stakeholders. Consolidation of these institutions need to be carried out by non-governmental organizations, i.e., Conservation International (Indonesia) Corridor Kaimana and local government, i.e., the Department of Marine and Fisheries, Department of tourism and culture along with Indigenous Peoples. So policy integration among sectors as well as the consistency and coherence should be coherent in the approach to building synergy with policies of sustainable management of turtle conservation in the region of Venu Island Wildlife Sanctuary, Kaimana, West Papua.